Melanoma in situ and syringoma: a rare collision tumor. Clinical-pathological report of a case - Pablo Umbert-Millet; Monica Quintana-Codina; Montse Salleras-Redonnet (Sociedade Brasileira de Dermatologia, 2017)
Abstract Collision or contiguous tumors, defined as two or more distinct tumors occurring at one site, are often an unexpected finding and may represent a diagnostic challenge, as clinical and histological presentations do not always coincide. Various combinations of collision tumors have been described with respect to melanocytic lesions, with the most frequently reported being the combination of nevus and basal cell carcinoma. We present an unusual case on the nose involving a melanoma in situ and a clinically-inapparent syringoma, which, to the best of our knowledge, is the first report of this combination.